2006
DOI: 10.1111/j.1365-2567.2006.02377.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of BAFF and APRIL in human B‐cell chronic lymphocytic leukaemia

Abstract: SummaryB-cell chronic lymphocytic leukaemia (B-CLL) is the most prevalent leukaemia in Western countries and is characterized by the gradual accumulation in patients of small mature B cells. Since the vast majority of tumoral cells are quiescent, the accumulation mostly results from deficient apoptosis rather than from acute proliferation. Although the phenomenon is relevant in vivo, B-CLL cells die rapidly in vitro as a consequence of apoptosis, suggesting a lack of essential growth factors in the culture med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
97
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 90 publications
(195 reference statements)
10
97
2
1
Order By: Relevance
“…CYP1B1 is a metabolic enzyme involved in degradation of environmental carcinogens like benzo(a)-pyrene and other polycyclic hydrocarbons (PAHs) present in environmental pollution and cigarette smoke which forms DNA adducts [22], and converts them to soluble products which are excreted out. Elevated CYP1B1 expression may result in a greater load of reactive oxygen intermediates (ROMs) causing genotoxic stress and tumour initiation [12,37]. There has been no report on the role of LAMA2 in cancer development; however from our studies we have observed a downregulation of LAMA2 expression.…”
Section: Transcription Regulationmentioning
confidence: 42%
“…CYP1B1 is a metabolic enzyme involved in degradation of environmental carcinogens like benzo(a)-pyrene and other polycyclic hydrocarbons (PAHs) present in environmental pollution and cigarette smoke which forms DNA adducts [22], and converts them to soluble products which are excreted out. Elevated CYP1B1 expression may result in a greater load of reactive oxygen intermediates (ROMs) causing genotoxic stress and tumour initiation [12,37]. There has been no report on the role of LAMA2 in cancer development; however from our studies we have observed a downregulation of LAMA2 expression.…”
Section: Transcription Regulationmentioning
confidence: 42%
“…APRIL and BAFF are two members of the TNF superfamily and show abnormally high expression levels in a number of B-cell malignancies, including mantle cell lymphoma, diffuse large cell lymphoma, and CLL. 39 APRIL binds to two of its receptors, TACI and BCMA (B-cell maturation antigen). 39 TACI and BCMA interact with various TRAF family members and activate the NF-kB pathway.…”
Section: Mir-15/16 Cooperates With Dleu7 In Cll Pathogenesismentioning
confidence: 99%
“…39 APRIL binds to two of its receptors, TACI and BCMA (B-cell maturation antigen). 39 TACI and BCMA interact with various TRAF family members and activate the NF-kB pathway. 39 Thus, NF-kB activation through TACI and BCMA may be an important pathway and is important in CLL pathogenesis.…”
Section: Mir-15/16 Cooperates With Dleu7 In Cll Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…According to various authors' studies, BAFF and APRIL molecules control homeostasis of B lymphocytes, their differentiation, maturation and survival in the physiological and pathological states, including neoplasms. It was proved that the increased expression of these molecules induced the development of B cells in chronic B-cell lymphocytic leukemia (B-CLL) [4,5]. TRAIL molecule was also found to play a role in the survival of B cells in B-CLL [6].…”
mentioning
confidence: 99%